1986
DOI: 10.1007/bf00008324
|View full text |Cite
|
Sign up to set email alerts
|

Studies on decomposition of two species of Salvina

Abstract: Decomposition of two species of Salvina, S. molesta Mitchell and S. cucullata Roxb. was studied for 220 days by the litter bag method. Salvinia molesta decomposes faster in the initial stages and S. cucullata in the later stages of decomposition. The release of nutrients is rapid during the first seven days and is ascribed to leaching. The rate of release of nutrients differs in the two species, with higher rates for P, Ca and Mg in S. molesta and for N in S. cucullata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…indicated that nutrient release was rapid during the initial four days and was attributed to physical leaching (Ogwada et al 1984;Sharma and Goel 1986;Asaeda and Nam 2002). This was followed by slow nutrient release attributed to microbial decomposition.…”
Section: Introductionmentioning
confidence: 95%
“…indicated that nutrient release was rapid during the initial four days and was attributed to physical leaching (Ogwada et al 1984;Sharma and Goel 1986;Asaeda and Nam 2002). This was followed by slow nutrient release attributed to microbial decomposition.…”
Section: Introductionmentioning
confidence: 95%
“…The decomposition of macrophytes is a complex process that is facilitated by microorganisms and invertebrates, and the action of these organisms starts the process of carbon and nutrient assimilation in food webs (Varga, 2003). Previous studies indicate that nutrient release is rapid during the initial 4 days of macrophyte decomposition due to physical leaching (Sharma and Goel, 1986; Asaeda and Nam, 2002), followed by a slower nutrient release phase due to microbial decomposition (Shilla et al ., 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The known detrimental environmental and economic impacts of S. molesta have caused it to be prohibited in the United States, and the U.S. Department of Agriculture has deemed it as one of the most noxious weeds in the country (Oliver 1993). The fast growth rate of S. molesta reduces the abundance of native plants as they compete for space and light (Sharma and Goel 1986). Additionally, slow decomposition rates reduce oxygen for young fish and other organisms (Hattingh 1961).…”
Section: Methodsmentioning
confidence: 99%